KEAWETAN ALAMI 57 JENIS KAYU INDONESIA DENGAN PENGUJIAN DI BAWAH NAUNGAN - Jasni Jasni (Pusat Penelitian dan Pengembangan Hasil Hutan, 2016)
Natural durability of 57 wood species originated from several regions in Indonesia was investigated outdoor under coverage. Initially, wood specimens were prepared from each species with dimension of 20 cm (length), 10 cm (width) and 2.5 cm (thickness). Specimens were placed on top of the bricks to avoid direct contact with soil, arranged randomly, and covered with crated-plastic sheets which served as protecting shades. Such experiment was conducted in research forest, Cikampek, West Java. Observation was conducted one year afterwards included evaluating the percentage of deteriorated wood specimens due to wood-destroying organisms. Results showed that after a year, 57 wood species could be categorized into five classes. Further scrutiny on each class revealed that four wood species belonged to class I (very durable); 16 wood species were class II (durable), 15 wood species class III (fairly durable), three wood species class IV (non-durable), and 19 wood species were classified as class V (perishable).